Artesunate regulates malignant progression of breast cancer cells via lncRNA TUG1/miR-145-5p/HOXA5 axis. - Chao Yang; Yunjiang Liu; Lingyun Gai; Ziteng Zhang; Yanshou Zhang; Geng Zhang; Kaiye Du; Chao Gao (PLoS ONE)
Background Breast cancer continues to be a predominant cause of female mortality globally, characterized by limited therapeutic options and substantial adverse effects. Artesunate (ART), a traditional Chinese medicine approved by the FDA for malaria treatment, has demonstrated potential anticancer properties against breast cancer. However, the underlying molecular mechanisms remain incompletely elucidated. This study posits that the antitumor efficacy of artesunate may be mediated through the regulation of the lncRNA TUG1/miR-145-5p/HOXA5 axis. Methods A comprehensive array of in vitro assays was employed to investigate the proposed molecular pathway, including CCK-8 proliferation assay, EdU incorporation assay, Transwell invasion assay, scratch wound healing assay, TUNEL apoptosis assay, and dual-luciferase reporter assay. Additionally, Western blot analysis, quantitative real-time PCR (qPCR), and plasmid transfection techniques were utilized to validate the findings. Results The results revealed that artesunate exerted a dose-dependent inhibitory effect on breast cancer cell proliferation. This was accompanied by the down-regulation of HOXA5, WNT, β-catenin, Fizz1, and Arg-1, implicating the involvement of the WNT/β-catenin signaling pathway. Furthermore, artesunate significantly modulated the expression levels of lncRNA TUG1, miR-145-5p, and HOXA5, suggesting a mechanistic role of the lncRNA TUG1 pathway in its anticancer activity. Conclusions These findings indicate that artesunate may inhibit breast cancer progression through the lncRNA TUG1/miR-145-5p/HOXA5 axis, highlighting its potential as a promising therapeutic candidate for future clinical trials in cancer therapy.